ANALISIS KELAYAKAN DAN STRATEGI PENGEMBANGAN BISNIS KEDAI KOPI ATMOSFER KOTA TARAKAN - Ferica Christinawati Putri (Jurnal Akuntansi, Ekonomi dan Manajemen Bisnis, 2021)
This study aims to determine the analysis and strategies used in developing the Atmospheric Coffee Shop business in the city of Tarakan. This type of research is descriptive using qualitative and quantitative approaches. The population in this study is Atmospheric Coffee Shops. The data collection used is by means of a questionnaire. Based on the results of the study, the business feasibility analysis for Atmospheric Coffee Shops in the city of Tarakan can be concluded that the BCR (Benefit Cost Of Ratio) is 1.20, FRR (Financial Rate Of Return) is 16.66%, PBP (Payback Period) is 6. Based on the eligibility criteria that have been determined can be said that the Atmospheric Coffee Shop business in the city of Tarakan is feasible to operate. While the stages of analysis carried out are by looking at the internal and external conditions of the company by means of situation analysis in other words, namely SWOT analysis, by going through the stages of IFAS (Internal Factor Analysis Summary), EFAS (External Factor Analysis Summary), SWOT diagrams and SWOT matrices. The results of the data analysis show that the strategy used is an aggressive strategy or SO (Strength-Opportunity) strategy.